Social media: A means of developing Generation Z's political participation in the digital era - Hariyanti, Hariyanti; Darmawan, Cecep; Rahmat, Rahmat; Anggraeni, Leni; Rafni, Al; Radini, Radini; Hasibuan, Hamdi Abdullah (Jurnal Civics: Media Kajian Kewarganegaraan, 2026)
This article examines how social media is utilised to enhance broader political participation among young people. The study employed a descriptive survey design using a Google Form, complemented by in-depth interviews conducted between September and December 2024. The participants consisted of 356 Generation Z individuals in Pekanbaru City, including first-time student voters and pre-voters. Data were analysed using descriptive techniques based on survey responses, expressed as percentages. The findings reveal three main typologies. First, social media functions as the primary source of political information due to its accessibility, practicality, up-to-date content, comprehensive coverage, and visually engaging format. Second, social media serves as a medium for political communication, where individuals engage by following political accounts, commenting on posts, or passively consuming content that still influences their daily discussions. Third, social media serves as a platform for political expression, as evidenced by reactions such as likes, dislikes, content sharing, and reporting. The study suggests that voter education actors should optimise their social media presence by producing engaging, accessible content aligned with current trends, such as podcasts, short videos, reels, and interactive Q&A formats. Collaboration with educational institutions and youth communities is also essential. Ultimately, these strategies aim to foster meaningful political participation among Generation Z, extending beyond electoral involvement to more active non-electoral engagement.